2006
DOI: 10.1177/0192636505283950
|View full text |Cite
|
Sign up to set email alerts
|

Meeting the Needs of Students With Disabilities: Experience and Confidence of Principals

Abstract: The purpose of this article is to examine the formal training of 205 principals in a variety of school districts in southern California. The data clearly define a need for increased training of principals in the area of special education during enrollment in preservice administration programs and while on the job. Preparation programs and school districts will find this information useful in establishing areas of training needs for their principals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(58 citation statements)
references
References 14 publications
3
55
0
Order By: Relevance
“…However, a wealth of evidence within the literature suggests the importance of the role of the principal in the provision of services to students with disabilities (Dyal, A., Flynt, S. W., & BennettWalker, D.,1996;Gameros, P.,1995;Lasky, B., & Karge, B. D., 2006;Ramirez, R. C., 2006). Further, the research on public school principals' attitudes toward the inclusion of students with disabilities can inform the current research on Catholic school principals' perceptions.…”
Section: Literature Review Principals and Attitudes Toward Serving Stmentioning
confidence: 99%
“…However, a wealth of evidence within the literature suggests the importance of the role of the principal in the provision of services to students with disabilities (Dyal, A., Flynt, S. W., & BennettWalker, D.,1996;Gameros, P.,1995;Lasky, B., & Karge, B. D., 2006;Ramirez, R. C., 2006). Further, the research on public school principals' attitudes toward the inclusion of students with disabilities can inform the current research on Catholic school principals' perceptions.…”
Section: Literature Review Principals and Attitudes Toward Serving Stmentioning
confidence: 99%
“…However, Wakeman et al (2006) found that middle school principals who reported higher levels of special education knowledge were more involved in special education instructional programs. Furthermore, research indicates the majority of principals feel poorly prepared for jobs as special education leaders (Bateman & Bateman, 2002;Crockett, 2002b;DiPaola & Walther-Thomas, 2003;Monteith, 2000) and report that their administrative preparation programs did not adequately prepare them to support teachers who instruct students with disabilities (DiPaola & Walther-Thomas, 2003;Lasky & Karge, 2006). This evidence suggests school leaders receive limited training regarding fundamental knowledge of special education, including special education instruction, and may be typically unprepared to provide effective special education instructional leadership (Kaye, 2002;Monteith, 2000).…”
Section: Principal Leadership and Special Educationmentioning
confidence: 99%
“…In addition, principals' positive instructional leadership behaviors affect teachers' perceptions of effective classroom instruction (Blasé & Blasé, 1999). However, survey studies reported elementary principals receive very limited preparation pertaining to special education, and in general, have limited knowledge of effective instructional practices for students with disabilities (Kaye, 2002;Lasky & Karge, 2006;Monteith, 2000;Wakeman et al, 2006). Furthermore, current instructional leadership models are characterized by the principal's active engagement in inspiring, educating, supporting, and collaborating with teachers to transform the quality of teaching and learning for all students (Glickman et al, 2001, Leithwood & Jantzi, 2000Sergiovanni & Starratt, 2007) and declare principals as the foundation for instructional leadership at the school level (Sergiovanni, 1998).…”
Section: Statement Of Problemmentioning
confidence: 99%
“…Lasky and Karge (2006) conducted a study to investigate principals' beliefs, formal training, and experiences they received when preparing for the principal position. The principals were specifically asked what information they received during their preparation program, what experiences they brought with them to train and prepare teachers, and how prepared they felt to carry out these responsibilities.…”
Section: Principals' Special Education Trainingmentioning
confidence: 99%
“…Lasky and Karge (2006) recommended that research-based standards be incorporated into principal preparation programs. Even though this study identified the importance of principal preparation programs, it would be beneficial to the field of education if a relationship could be identified between training and the implementation of special education programs.…”
Section: Principals' Special Education Trainingmentioning
confidence: 99%